AJET bibliometrics and licensing - Heinrich, Eva; Henderson, Michael; Redmond, Petrea (Australasian Journal of Educational Technology, 2019)
In this editorial we present the bibliometric data and explain the new Creative Commons license being adopted from Volume 36. The bibliometrics include the journal’s publication, review and article access statistics, the articles attracting the most interest over the past year and the citation performance of the journal.